First, solve one equation for one variable...
-3x + y = 10
y = 3x + 10
Now, put that into the other equation.
9x + 5y = 2
9x + 5(3x + 10) = 2
9x + 15x + 50 = 2
24x = -48
x = -2
Now, put that back into one of the equations to find the missing variable...
y = 3x + 10
y = 3(-2) + 10
y = 4
The solution is (-2, 4)
2007-05-16 22:26:17
·
answer #1
·
answered by Mathematica 7
·
0⤊
0⤋
9x+5y=2
-3x+y=10
therefore, y=10+3x
subsitute the value of y in first equation
9x+5(10+3x)=2
9x+50+15x=2
24x=2-50
24x=-48
x=-2
put the value of x in 2nd equation
-3(-2)+y=10
6+y=10
y=4
2007-05-17 05:30:14
·
answer #2
·
answered by DAN G 1
·
0⤊
0⤋
First, solve one equation for one variable...
-3x + y = 10
y = 3x + 10
Now, put that into the other equation.
9x + 5y = 2
9x + 5(3x + 10) = 2
9x + 15x + 50 = 2
24x = -48
x = -2
Now, put that back into one of the equations to find the missing variable...
y = 3x + 10
y = 3(-2) + 10
y = 4
The solution is (-2, 4)
2007-05-17 05:32:09
·
answer #3
·
answered by kk kk kk 2
·
0⤊
0⤋
9x +5y=2
-3x+y=10
therefore by solving 2 equation
y=3x+10 .....3
therefore substituting it in 1 equ
9x+5(3x+10)=2
9x+15x+50=2
24x=2-50
x=-48/24
x=-2
substituting in equ.3
y=3*-2+10
y=-6+10
y=4
2007-05-17 06:11:46
·
answer #4
·
answered by neha 1
·
0⤊
0⤋
9x + 5y = 2
-3x + y = 10
pick one to solve for a variable.
in this case i chosed. -3x + y = 10
-3x + y = 10
y=3x+10
now plug it back in to top eqn.
9x+5(3x+10)=2
solve for x, then plug back into bottom eqn and solve for y
easy right!!?
2007-05-17 05:28:31
·
answer #5
·
answered by electric 3
·
0⤊
0⤋
y = 3x + 10
9x + 15x + 50 = 2
24x = - 48
x = - 2
y = - 6 + 10 = 4
x = - 2, y = 4
2007-05-17 06:06:01
·
answer #6
·
answered by Como 7
·
0⤊
0⤋